Denitrifying activity of activated sludge in suspension and in biofilm - Cortez, Susana (2008)
[Excerpt] Denitrification consists in the reduction of oxidized nitrogen compounds like nitrite or nitrate to gaseous nitrogen compounds. Most of biological denitrification processes rely on heterotrophic microorganisms and therefore the use of methanol, ethanol, glucose, citrate or acetate as a carbon source is needed. Activated sludge is currently the most widely used process for the treatment of both domestic and industrial wastewaters. Attached to a support sludge microorganisms develop an active thin layer known as biofilm, which has many advantages like high biomass concentration and resistance to short-term toxic loads when compared with suspended growth processes. The aim of the present work is to compare the denitrifying activity of an adapted consortium of activated sludge in the form of planktonic cells with its biofilm form. [...]